Hippocampal Asymmetry Increases with Age - Florian Kurth; Eileen Luders (MDPI AG, 2023)
It is unclear whether differences between the two brain hemispheres become larger or smaller with increasing age. Given that the hippocampus is particularly susceptible to age-related changes, here, we set out to investigate the correlation between chronological age and hippocampal asymmetry, both for the hippocampal complex as a whole and in cytoarchitectonically defined subregions (cornu ammonis 1, 2, 3, dentate gyrus, subiculum, and entorhinal cortex). We analyzed T1-weighted data of the brain from a sample of 725 healthy individuals (406 women/319 men) spanning a wide age range (36-100 years) from The Lifespan Human Connectome Project in Aging. Correlations between the absolute asymmetry index and chronological age were positive for all six subregions and also for the hippocampal complex as a whole, albeit effects the effects were not significant for the dentate gyrus. This suggests that, overall, hippocampal asymmetry increases with increasing age (i.e., the left and right hippocampi become more different over time). Given that the subregions of the hippocampal complex serve different brain functions, follow-up research is needed to explore the functional implications within the framework of brain aging. In addition, longitudinal studies will be necessary to confirm the observed cross-sectional effects.